The effect of tourism promotion, prices and facilities on visitors' satisfaction of sweet water beach tourism padang - Rifki Wahyudi; Irdha Yusra (Marketing Management Studies, 2021)
This study aims to examine the effect of promotions, prices and tourist facilities on the satisfaction of visitors to Padang's Sweet Air Coast. This type of research is quantitative. Sampling using the Slovin formula so that the number of samples obtained is 100 people. The types of data used in this research are quantitative and qualitative data. While the data sources are primary and secondary data sources. The data analysis technique uses validity and reliability tests using the SPSS version 16.00 program. The hypothesis was tested using the t test at = 0.05. The results of this study indicate that promotion and price have a positive and significant effect on visitor satisfaction of Padang Air Sweet Beach tourism. Meanwhile, tourist facilities have no significant effect on the satisfaction of visitors to the Padang Air Sweet Beach tourism.